2012
DOI: 10.5032/jae.2012.02087
|View full text |Cite
|
Sign up to set email alerts
|

Instructor Verbal and Nonverbal Immediacy and the Relationship with Student Self–efficacy and Task Value Motivation

Abstract: This descriptive correlation study sought to examine the relationships between verbal immediacy, nonverbal immediacy, self-efficacy and task value. Respondents assessed the verbal and nonverbal immediacy of their course instructor, and then assessed their personal self-efficacy and task value motivation. Results showed a significant positive relationship between verbal immediacy and self-efficacy (r = .334), nonverbal immediacy and self-efficacy (r = .209), verbal immediacy and task value (r = .234), and nonve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 30 publications
0
27
0
2
Order By: Relevance
“…The five-point scale and descriptors are described in Table 2. Previous research utilizing the present form of the NIB reported summated reliability coefficient estimates ranging from .82 to .94 (Christophel, 1990;McCroskey et al, 1996;Titsworth, 2004;Velez & Cano 2007;Velez, 2008).…”
Section: Instrumentationmentioning
confidence: 82%
See 4 more Smart Citations
“…The five-point scale and descriptors are described in Table 2. Previous research utilizing the present form of the NIB reported summated reliability coefficient estimates ranging from .82 to .94 (Christophel, 1990;McCroskey et al, 1996;Titsworth, 2004;Velez & Cano 2007;Velez, 2008).…”
Section: Instrumentationmentioning
confidence: 82%
“…The present study employed a one-measurement cross-sectional survey design (Creswell, 2009;Spector, 1981) where undergraduate student subjects completed a paper questionnaire to acquire their perceptions of the primary variables of course engagement and teacher verbal and nonverbal immediacy behaviors. To appropriately account for student perceptions, a five-point unipolar scaled question structure was utilized consistent with previous studies examining the constructs of student course engagement (Handelsman, Briggs, Sullivan, & Towler, 2005;Svanum & Bigatti, 2009) and teacher immediacy behaviors (Christophel, 1990;Gorham, 1988;Velez, 2008). The University of Missouri Institutional Review Board (IRB) reviewed and approved the present study and data collection procedures prior to instrument administration.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations